The Great African Slave Revolt of 1825 : Cuba and the Fight for Freedom in Matanzas - Barcia Paz, Manuel, 1972- (Book collections on Project MUSE., 2012)
In June 1825 the Cuban countryside witnessed a large African-led slave rebellion--a revolt that began a cycle of slave uprisings lasting until the mid-1840s. The Great African Slave Revolt of 1825 examines this movement and its participants for the first time, highlighting the significance of African warriors in New World plantation society. Unlike previous slave revolts--led by alliances between free people of color and slaves, blacks and mulattoes, Africans and Creoles, and rural and urban populations--only African-born men organized the uprising of 1825. From this year onwards, Barcia argues, slave uprisings in Cuba underwent a phase of Africanization that concluded only in the mid-1840s with the conspiracy of La Escalera, a large movement organized by free colored men with ample participation of the slave population. The Great African Slave Revolt of 1825 offers a detailed examination of the sociopolitical and economic background of the Matanzas rebellion, both locally and colonially. Based on extensive primary sources, particularly court records, the study provides a microhistorical analysis of the days that preceded this event, the uprising itself, and the days and months that followed. Barcia gives the Great African Revolt of 1825 its rightful place in the history of slavery in Cuba, the Caribbean, and the Americas.